The Implementation of Integrated Antenatal Care In BEmNOC and non-BEmNOC Health Service In Semarang - Suryani Yuliyanti; Putri Vinorica; Ratnawati Ratnawati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
The maternal mortality rate in Central Java is ranked 4th in Indonesia. Implementation of quality Antenatal Care (ANC) can reduce maternal mortality (MMR) through early detection in pregnancy. ANC services can be carried out both at BEmNOC (Basic Emergency Obstetric Care) and non-BEmNOC primary health care services (PHC). All PHC are given the same authority in terms of early detection and services for pregnant women. This study aims to determine the relationship of the health centers status and the implementation of integrated antenatal care in the Semarang municipality. This was a cross sectional design carried out on 140 samples taken by consecutive sampling divided into primary health care services BEmNOC and non-BEmNOC 70 samples each. The implementation of integrated ANC was measured using 50 checklists consisting of 13, 12 and 25 checklist of first, second and third trimester sequentially and divided in two value namely do and not do. The relationship between the health center status and the implementation of the integrated ANC was further analyzed by Chi-square test using SPSS 22 software. The study found that the number of samples implementing an integrated ANC in the BEmNOC PHC group was 81.4% (57 samples) while the non-BEmNOC PHC group was 32.9% (23 samples). Chi-square test showed a significant difference between the status of the PHC and the implementation of the ANC (p = 0,000; PR value = 2.47). It was concluded that there was a significant correlation between the health center status and the implementation of ANC in Semarang municipality.